(untitled) (Archaeologia Adriatica, 2008)
According to Appian of Alexandria, on the occasion of his triumph in 46 BC Caesar had an attractive image of Cleopatra erected in the temple of Venus Genetrix, which in the writer’s time still stood there. Cassius Dio in the description of Octavian’s triumph in 29 BC mentioned a golden Cleopatra, which in his time could be seen in the temple of Aphrodite. The difference between the two sources has led to conflicting interpretations in the literature. Some claim that Caesar had a golden statue of Cleopatra placed in the temple of Venus Genetrix. Others assert that the statue arrived as Egyptian loot and was placed there by Octavian, and Appian by mistake attributed this to Caesar. The analysis shows that both authors were writing as eyewitnesses. Appian’s account is precise and aids in understanding Dio’s text. When they are viewed together, it can be concluded that Caesar had a statue of Cleopatra placed by the cult statue of Venus Genetrix, which in the 2nd century AD was considered to exist in the original form. One eyewitness considered it beautiful, the other that it glittered with gold. The statue was erected when the powerful pair had heirs and were at the peak of power. It had to be befitting to the Roman shrine so as to contribute to the propaganda effects of the Julian sacral complex. The Ptolemaic tradition of depicting the members of the ruling house and the popularity of the cult of Isis in Rome offered a model: a Hellenistic Isis or priestess of Isis with the face of Cleopatra could be interpreted as a worshipper of Venus or as a goddess similar to Venus. The attitudes of the Romans to Cleopatra and Egypt, and to Isis and her cult varied, but the statue remained as part of the earliest fittings of the temple that was a holy place of the imperial rulers. In the periods of Appian and Dio, the cult of Isis was widely accepted. Similar statues were numerous, so the one in the temple of Venus Genetrix was named after Cleopatra, as the portrait differed from the others.